Ageing with cancer: Exploring the nature, influences, and experiences of unmet needs among older adult cancer survivors - Boland, Vanessa; Drury, Amanda (Elsevier, 2025)
Background: Older adults (≥65 years) represent the largest demographic diagnosed with cancer, yet they remain underrepresented in research. Older adults experience unique challenges in cancer care due to multi-morbidity, social support, and fragmented healthcare services. There is limited evidence regarding the unmet needs of older adults with cancer, particularly those with haematological malignancies. Methods: A concomitant mixed methods study was undertaken, involving a cross-sectional questionnaire (n=84) and semi-structured interviews (n=8). Participants were older adult survivors of cancer or haematological malignancies recruited from five hospitals and advocacy organisations across Ireland. Quantitative data were analysed using descriptive and inferential statistics; qualitative data were analysed thematically using Braun and Clarke’s approach. Results: Participants ranged in age from 65 to 89 years old; 53% were living with a haematological malignancy. The most common unmet needs included fatigue (47%), feeling normal (40%), memory or focus difficulties (39%), stress (36%), and anxiety about treatment outcomes (37%). Qualitative findings highlighted challenges in access to care, including travel difficulties, high costs, and limited public transport. While continuity of care was mostly described as positive post-diagnosis, delays in diagnosis were common. Emotional needs centred on a desire for independence, fear of recurrence, and reliance on family or healthcare professionals. Most participants were retired, and many described financial concerns related to welfare entitlements. Information needs varied; while treatment side effects were well explained, guidance on lifestyle and wellbeing was inconsistent. Conclusions: Older adults living with and after cancer experience a range of unmet needs, particularly around fatigue, emotional wellbeing, continuity of care, and accessible information. While participants valued relationships with healthcare professionals and support services, gaps in pre-diagnosis care, support for travel to care, and information needs persist. Findings highlight the need for age-sensitive interventions and support tools tailored to this population.
Annals of Oncology
EONS18
PUBLISHED
Berlin
Keywords: Cancer; Ageing; Cancer Survivorship